2019
DOI: 10.1155/2019/9214186
|View full text |Cite
|
Sign up to set email alerts
|

Triggering WORM/SRAM Memory Conversion by Composite Oxadiazole in Polymer Resistive Switching Device

Abstract: Electrical characterization indicates that the nonvolatile write once read many (WORM) times/volatile static random access memory (SRAM) conversion was triggered by the composite of the oxadiazole small molecule. FTO/PMMA/Ag device possesses nonvolatile WORM memory behavior, while the FTO/PMMA+oxadiazole/Ag device shows vastly different volatile SRAM feature. The FTO/PMMA/Ag and FTO/PMMA+oxadiazole/Ag memory devices both exhibit high ON/OFF ratio nearly 104. The additive oxadiazole small molecule in the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The detailed electrical analysis indicated that the ERSM behavior could be attributed to the electronic switching mechanism mediated by the electron trapping/detrapping [9]. A polymer memristor with buffer layer was prepared in [10], and its specific working mechanism indicated that the device also belonged to ERSM. In [11], the design and fabrication of an asymmetrical Al/TiO2/FTO sandwiched nanostructure was reported by using simple spin-coating and vacuum deposition techniques.…”
mentioning
confidence: 99%
“…The detailed electrical analysis indicated that the ERSM behavior could be attributed to the electronic switching mechanism mediated by the electron trapping/detrapping [9]. A polymer memristor with buffer layer was prepared in [10], and its specific working mechanism indicated that the device also belonged to ERSM. In [11], the design and fabrication of an asymmetrical Al/TiO2/FTO sandwiched nanostructure was reported by using simple spin-coating and vacuum deposition techniques.…”
mentioning
confidence: 99%